PENERAPAN ALGORITMA GENETIKA UNTUK PENJADWALAN MENGAJAR GURU (STUDI KASUS : MA UMMUL RODHIYAH TANGERANG) - Apsoh Nurjanah; Pradnyana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Scheduling is a priority activity for teachers or teachers based on their respective skill levels and to divide tasks we need to pay attention to whether or not there is piles and additional time for teachers who teach subjects to students. In the aspect of teaching activities it is very important for the smooth running of the teaching and learning process in schools, and sometimes time is often piled up for teachers. Therefore it is necessary to schedule special teachers or teachers to avoid piles and increase in time and support the implementation of activities related to teaching and learning. In the case of teaching scheduling, a better algorithm is needed, namely the genetic algorithm which is one of the most appropriate algorithms used to solve complex optimization problems that are difficult to do by conventional methods.